Avaliação da formação de biofilme e sensibilidade ao ácido peracético por Salmonella spp. isolada de abatedouro avícola - Vivian, Ricardo Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Despite recent technological advances in the food industry, still observed the occurrence of numerous food borne illnesses due to ingestion of contaminated by pathogenic microorganisms, including members of the genus Salmonella spp. Among the products involved in processes of contamination by this agent, the steaks are the most important, being the vehicle of birds in numerous cases of human infections. In addition to problems in public health, the microorganism causes big problems due to the formation of biofilms in the industry, and this occurs because of the accession of microorganisms on a surface of contact, which are fixed, are an array of exopolysaccharides and begin their growth. These are a concern to the food industry for its effect as a source of chronic infection, which increases the chances of placement of the pathogen to the consumer. There are many factors that affect biofilm development, entres they the type of surface and its physicochemical properties, since they will directly influence the adhesion of microorganisms. Several control measures to solve the problem are employed in the industry, such as the use of sanitizers, featured in the peracetic acid, though they have proven their effect on sessile cells in biofilms its action still needs more scientific evidence. In this sense, the data obtained from this study confirm the importance of Salmonella spp. as forming biofilm on different surfaces, which can induce a greater permanence of these microorganisms in the processing environment in the industry and hence a greater chance of food contamination, with risks to the consumer. Our results also confirmed that the physicochemical surface properties of different materials directly influence the adhesion of microorganisms and, consequently, the development of the biofilm. In simple terms, the greater the hydrophobicity of the surface, the greater the ability to promote the development of the biofilm, in order that the ...

Apesar dos recentes avanços tecnológicos na indústria de alimentos, ainda se observa a ocorrência de inúmeras enfermidades de origem alimentar, devido à ingestão de alimentos contaminados por micro-organismos patogênicos, dentre eles os do gênero Salmonella. Dentre os produtos envolvidos em processos de contaminação por este agente, as carnes são as mais importantes, sendo a de aves o veículo em numerosos casos de infecções humanas. Além dos problemas em saúde pública, o micro-organismo causa grandes problemas devido à formação de biofilmes na indústria, sendo que esta ocorre em virtude da adesão dos micro-organismos em uma superfície de contato, a qual se fixam, constituem uma matriz de exopolissacarídeos e iniciam seu crescimento. Estes representam uma preocupação à indústria de alimentos por seu efeito como fonte de contaminação crônica, que aumenta as chances de veiculação do patógeno ao consumidor. Inúmeros são os fatores que condicionam o desenvolvimento do biofilme, entres eles o tipo de superfície e suas propriedades físico-químicas, já que as mesmas exercem influência direta sobre a adesão dos micro-organismos. Diversas medidas de controle para resolver o problema são empregadas na indústria, como o uso de sanitizantes, em destaque os à base de ácido peracético, que embora tenham o seu efeito sob células sésseis comprovado, a sua ação sob biofilmes ainda necessita de maior comprovação científica. Nesse sentido, os dados obtidos por este trabalho ratificaram a importância de Salmonella spp. como formadora de biofilme em diferentes superfícies, o que pode induzir a uma maior permanência destes micro-organismos no ambiente de processamento na indústria e, consequentemente, a uma maior chance de contaminação dos alimentos, com riscos ao consumidor. Nossos resultados também confirmaram que as propriedades físico-químicas da superfície dos diferentes materiais influenciaram ...
Keywords: Salmonella; Biofilme; Ácido peracético; Desinfecção e desinfetantes; Biofilms